2018
DOI: 10.1172/jci98819
|View full text |Cite
|
Sign up to set email alerts
|

Disease-driving CD4+ T cell clonotypes persist for decades in celiac disease

Abstract: Little is known about the repertoire dynamics and persistence of pathogenic T cells in HLA-associated disorders. In celiac disease, a disorder with a strong association with certain HLA-DQ allotypes, presumed pathogenic T cells can be visualized and isolated with HLA-DQ:gluten tetramers, thereby enabling further characterization. Single and bulk populations of HLA-DQ:gluten tetramer-sorted CD4+ T cells were analyzed by high-throughput DNA sequencing of rearranged TCR-α and -β genes. Blood and gut biopsy sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
141
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 34 publications
5
141
0
1
Order By: Relevance
“…In the last PCR reaction, TRAC and TRBC barcoding primers were added together with Illumina PairedEnd primers. Cycling conditions, concentrations and primer sequences for all three PCR reactions can be found in (Risnes et al, 2018), and original protocol in (Han et al, 2014). Products in each well were combined, purified and sequenced using the Illumina paired-end 250 bp MiSeq platform at the Norwegian Sequencing Centre (NSC), at Oslo University Hospital.…”
Section: Single-cell Tcrα-β Sequencingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the last PCR reaction, TRAC and TRBC barcoding primers were added together with Illumina PairedEnd primers. Cycling conditions, concentrations and primer sequences for all three PCR reactions can be found in (Risnes et al, 2018), and original protocol in (Han et al, 2014). Products in each well were combined, purified and sequenced using the Illumina paired-end 250 bp MiSeq platform at the Norwegian Sequencing Centre (NSC), at Oslo University Hospital.…”
Section: Single-cell Tcrα-β Sequencingmentioning
confidence: 99%
“…Products in each well were combined, purified and sequenced using the Illumina paired-end 250 bp MiSeq platform at the Norwegian Sequencing Centre (NSC), at Oslo University Hospital. The resulting paired-end sequencing reads were processed in a multistep pipeline using selected steps of the pRESTO toolkit (Vander Heiden et al, 2014) according to (Risnes et al, 2018). In short, high-purity reads (average Phred score >30) were deconvoluted using barcode identifiers and collapsed, and only the top three for each well were retained for further analysis.…”
Section: Single-cell Tcrα-β Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Having confirmed that cell-surface pMHC was specifically detected both on in vitro peptideloaded cells and on patient-derived APCs loaded in vivo, we wondered if we could block the interaction between T cells and APCs. We focused on the DQ2.5-glia-α2 epitope, as it is the most extensively characterized gliadin T-cell epitope to which all patients mount a T-cell response (29).…”
Section: High Affinity Antibodies Are Potent Inhibitors Of T-cell Actmentioning
confidence: 99%